2003
DOI: 10.1074/jbc.m309183200
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Localization, Oligomerization, and Phosphorylation Are Required for Optimal Raf Activation

Abstract: Activation of the serine/threonine kinase c-Raf-1 requires membrane localization, phosphorylation, and oligomerization. To study these mechanisms of Raf activation more precisely, we have used a membrane-localized fusion protein, myr-Raf-GyrB, which can be activated by coumermycin-induced oligomerization in NIH3T3 transfectants. By introducing a series of point mutations into the myr-Raf-GyrB kinase domain (S338A, S338A/Y341F, Y340F/Y341F, and T491A/S494A) we can separately study the role that membrane localiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…RAF dimerization-mediated signaling was first suggested by the observation that artificial dimerization activates RAF (17, 18). Next, immunoprecipitation (IP) suggested that formation of homo-and heterotypic RAF "dimers" is associated with active RAS (15,16,19). X-ray crystallography of the BRAF catalytic domain (CatB) identified critical residues postulated to enable CatB-CatB dimer formation (11).…”
mentioning
confidence: 99%
“…RAF dimerization-mediated signaling was first suggested by the observation that artificial dimerization activates RAF (17, 18). Next, immunoprecipitation (IP) suggested that formation of homo-and heterotypic RAF "dimers" is associated with active RAS (15,16,19). X-ray crystallography of the BRAF catalytic domain (CatB) identified critical residues postulated to enable CatB-CatB dimer formation (11).…”
mentioning
confidence: 99%
“…[51][52][53][54] We therefore examined, whether dynamic changes of A-Raf localization impact on MST2 binding. For this purpose, we used the rapalogue (AP21967)-inducible heterodimerization system, which permits the efficient and selective cross-linking of FRB and FKBP-tagged proteins, 55,56 We co-expressed a flag-tagged FRB A-Raf Figure S3).…”
Section: Resultsmentioning
confidence: 99%
“…Upon activation through growth factors, dephosphorylation at the cell membrane by PP2A and PP1 phosphatases releases 14-3-3 from Raf thereby enabling Ras binding and membrane recruitment. 51,53,[65][66][67] However, due to the exchange of an arginine for a lysine at position 22 in its RBD and a non-conserved tyrosine 296 in the N-region, A-Raf is only weakly activated by oncogenic H-Ras. 9,68 In addition, several phosphorylation sites between amino acids 248 and 267 seem to facilitate A-Raf dissociation from the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
“…The phosphorylation sites Ser 338 SYY 341 , are essential for full kinase activation and for interaction with the substrate MEK (40 -42) . Phosphorylation of Ser338 stimulated by growth factor is Ras-dependent and is necessary for maximal C-Raf activation (4,40,43,44) . A recent report indicated that Ser338 could be an autophosphorylation site induced by the dimerization of C-Raf or heterodimerization of C-Raf and B-Raf (45) or be a target for casein kinase 2 (CK2) recruited to Raf-1 and B-Raf by the scaffold kinase suppressor of Ras (KSR) (46) .…”
Section: Ras-dependent Activation Of Raf Kinasementioning
confidence: 99%
“…The kinases that can be involved in the phosphorylation of Tyr341 include the Src (47,17) and JAK family kinases (Janus Kinase) (48) . Phosphorylation of Tyr340/341 stimulated by growth factor requires Ras-dependent membrane recruitment and Src family tyrosine kinases (18,19,40,45) , and phosphorylation of Tyr340/341 and Ser338 is required for maximal Raf activity (4,8,43,44) . Mutation of Tyr341 severely compromises Raf-1 kinase activity (47,17) .…”
Section: Ras-dependent Activation Of Raf Kinasementioning
confidence: 99%